Characteristics of oil and gas distribution and controlling factors of hydrocarbon accumulations in the Eocene Pinghu formation of the Xihu Depression, East China Sea - Kaifei, Liao; Kai, Zhong; Yi, Lu; Goh, Thian Lai; Lee, Khai Ern (Penerbit Universiti Kebangsaan Malaysia, 2024)
The Xihu Depression at the shelf of the East China Sea is a petroliferous basin with excellent exploration potential. The Eocene Pinghu Formation has become a recent oil and gas exploration target and as the critical hydrocarbonbearing stratigraphic layer in the basin. However, studies specifically examining the characteristics of hydrocarbon distribution and the controlling factors of reservoirs in the Kongqueting area remain limited. The lack of in-depth hydrocarbon accumulation model research restricts subsequent exploration. In this paper, based on data from drilling, 3D seismic, well test, and geochemical analysis, we found that coal bed-related hydrocarbon source rocks were widely occurred in the Pinghu Formation in the Kongqueting area. The source rocks provide good hydrocarbon supply of near-source and distant-source to reservoir. The river sands were connected laterally and stacked vertically, forming a pattern characterized by ‘lateral succession and vertical superposition’ indicative of good quality of reservoir. During the deposition period of the Pinghu Formation, two large sets of regional cap rock (P3 and P7) were excellent sealing rock. The sand reservoir was interbedded with shale layers, forming a Mille-feuille type of reservoir-seal pair. Faults formed at the early stage of the formation of basin serve as conduits for hydrocarbon migration, governing both the spatial distribution of hydrocarbon-bearing strata and the types of hydrocarbon accumulations. These faults were instrumental in facilitating the formation of extensive oil and gas accumulations. This paper establishes a hydrocarbon accumulation model in the Kongqueting area, characterized as ‘dual hydrocarbon supply from source, upper oil, and lower gas, good reservoir-seal pair, hydrocarbon migration through fault conduit’.